TECHNICAL AND ECONOMIC FEASIBILITY OF SOLAR IRRIGATION PUMPING SYSTEM: A REVIEW - DIOP, Lamine (Knowledge-Based Engineering and Sciences, 2020)
Climate change has become a major constraint to the development of rain-fed agriculture due to the decline of rainfall. Therefore, irrigated agriculture is an alternative allowing farmers to have more access to water in order to meet crop water requirements. However, irrigated agriculture faces a major constraint related to the accessibility of energy sources used in pumping water. In general, the most common energy sources used in pumping water for irrigation are fuel and electricity. Nevertheless, they are very expensive, are not always accessible particularly in rural areas in Africa and have a negative impact on the environment; hence the need to find alternatives to solve this problem. This review focuses on the technical and economic feasibility of solar irrigation pumps and the impact of their use on the environment. Several aspects related to solar pumping have been discussed, namely the components of the solar pumping system, the energy source used, the principle of operation of the system, the technical, economic, and environmental feasibility. Reviews show that the use of solar irrigation pumps is a technically and economically feasible alternative in several areas with less environmental impact.